Effectiveness of Internal Control of Supplier Debt Payment at Hotel X - ANJANI, Anak Agung Istri Puspita; SEPTIVIARI, Anak Agung Istri M. (Journal of Governance, Taxation and Auditing, 2025)
This study aims to analyze the effectiveness of supplier debt payments at Hotel X. The method used in this research is descriptive qualitative, which involves direct analysis of field data using relevant theoretical concepts. Data were collected through observation, interviews, and documentation. The internal control framework developed by Mulyadi was employed to analyze the data. The results show that the internal control system for supplier debt payments at the Hotel. Of the four indicators and twelve criteria, only one criterion, job rotation, was not fulfilled. This outcome indicates that most aspects of internal control have been implemented optimally. However, despite being categorized as highly effective, delays in supplier payments still occur. This is primarily due to the fact that the accounts payable section is currently managed by only one staff member, who is fully responsible for all processes, including invoice review, document verification, and payment execution. The effectiveness of internal control over supplier debt payments at Hotel X is very effective. Based on the four indicators with a total of twelve criteria, the overall average score reached 96%, indicating that the internal control system at Hotel X, particularly in the accounts payable section, is categorized as "very effective", as it falls within the effectiveness percentage range of 81%–100%.